Epidemiology of Rotavirus diarrhea in children under five: A hospital-based surveillance in Jakarta - Muzal Kadim; Yati Soenarto; Badriul Hegar; Agus Firmansyah (Indonesian Pediatric Society, 2011)
Background Rotavirus is still a major cause of acute diarrheaÂ in children around the world, both in developed and developingcountries. WHO Surveillance from 2001 to 2008 showed that inÂ children under five years of age treated for acute diarrhea, on averageÂ 40% of cases were caused by rotavirus. A previous study in IndonesiaÂ showed that the incidence of rotavirus diarrhea in children rangedÂ from 20%ô€‘60% of diarrhea cases. However, there have been fewÂ studies identifying the genotypes of rotavirus strains in Indonesia.Â This infonnation is indispensable for manufacturing vaccines.Objective To examine the epidemiology of rotavirus diarrhea,Â including genotypes and clinical characteristics, in children underÂ five years who were hospitalized in Jakarta.Methods This study was a prospective surveillance conductedÂ at Cipto Mangunkusumo Hospital, Jakarta from January toÂ December 2007 investigating hospitalized children under fiveÂ years of age who suffered from acute diarrhea.Results Ninetyô€‘nine patients joined the study. The incidence ofÂ rotavirus infection in this study was 67%. The youngest was 2months of age and the oldest 54 months of age, Mth an average ageÂ of 13.6 months. As much as 92% of rota virus diarrhea was foundÂ in subjects aged 3ô€‘23 months, Mth a peak age of 12ô€‘23 months.Â Nutritional status, degree of dehydration, bloating, fever, bloodÂ in stool, and mucus in the feces were not significantly differentÂ between rotavirus and nonô€‘rotavirus diarrhea. Vomiting tended toÂ be more frequently experienced by children Mth rotavirus diarrheaÂ than those with nonô€‘rotavirus (88% vs. 67%). There was no clear,Â seasonal pattern for rotavirus diarrhea. Most G genotypes in thisÂ study were G1 (35%), G9 (12.5%), G2 (7.5%) and the majority ofÂ P genotypes were P6 (52.5%), P8 (17.5%) and P4 (10%).Conclusions The incidence of rotavirus diarrhea in hospitalizedÂ children under five years of age in Jakarta was 67%, with apredominance ofG1, G9 and G2 genotypes.Â